2021
DOI: 10.1002/app.51187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified layered double hydroxide on the flammability of intumescent flame retardant PP nanocomposites

Abstract: The dodecyl sulfate intercalated CaMgAl-hydrotalcites (layered double hydroxides [LDHs]) were successfully prepared by co-precipitation method, and characterized by X-ray diffraction analysis, infrared spectroscopy (Fourier transform infrared spectra [FT-IR]), thermogravimetry (TG-DTA), scanning electron microscope, and BrunnerÀEmmetÀTeller (BET). The prepared LDHs were added to the intumescent flame retardant (IFR) polypropylene (PP) nanocomposites, and the limiting oxygen index method (LOI), vertical combust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Synergists can be used with IFR such as nano-SiO 2 , montmorillonite (MMT), 4A zeolite, layered double hydroxides (LDHs), and carbon materials. [23][24][25][26][27][28] Ji et al [29] added 10 wt% IFR and 1 wt% CNTs into the TPU; LOI was 30.1% and passed the UL-94 V-0 rating, compared with 10 wt% IFR (LOI 28.0%, UL-94 V-2 rating) and 15 wt% IFR (LOI 30.1%, UL-94 V-2 rating), which indicated that a spot of CNTs had a synergistic flame retardant effect with IFR. Chen et al [30] used fumed silica to synergize with ammonium polyphosphate (APP) in the TPU; LOI was 32.3% with 18.75 wt% APP and 1.25 wt% fumed silica.…”
mentioning
confidence: 99%
“…Synergists can be used with IFR such as nano-SiO 2 , montmorillonite (MMT), 4A zeolite, layered double hydroxides (LDHs), and carbon materials. [23][24][25][26][27][28] Ji et al [29] added 10 wt% IFR and 1 wt% CNTs into the TPU; LOI was 30.1% and passed the UL-94 V-0 rating, compared with 10 wt% IFR (LOI 28.0%, UL-94 V-2 rating) and 15 wt% IFR (LOI 30.1%, UL-94 V-2 rating), which indicated that a spot of CNTs had a synergistic flame retardant effect with IFR. Chen et al [30] used fumed silica to synergize with ammonium polyphosphate (APP) in the TPU; LOI was 32.3% with 18.75 wt% APP and 1.25 wt% fumed silica.…”
mentioning
confidence: 99%
“…From Figure 6b, the decomposition rate of MZBMSO/P(POSS‐MAA)‐LDHs treated leather was much faster than that of MZBMSO treated leather, but the temperature of MZBMSO/P(POSS‐MAA)‐LDHs treated leather at maximum degradation rate was higher than MZBMSO treated leather. This indicated that P(POSS‐MAA)‐LDHs played the role of catalytic carbonization when exposed to heat, and formed a barrier on the surface of collagen fibers, thereby improving the heat resistance of collagen fibers 42 . The results showed that the introduction of P(POSS‐MAA)‐LDHs enabled to improve the thermal stability of leather 43 …”
Section: Resultsmentioning
confidence: 91%
“…This indicated that P(POSS-MAA)-LDHs played the role of catalytic carbonization when exposed to heat, and formed a barrier on the surface of collagen fibers, thereby improving the heat resistance of collagen fibers. 42 The results showed that the introduction of P(POSS-MAA)-LDHs enabled to improve the thermal stability of leather. 43 The cone calorimeter is the most ideal instrument that characterize the combustion performance of materials, and the data enable to be used to evaluate the combustion behavior of materials in a fire.…”
Section: Flame Retardant Performance Of Leather After Fatliquoringmentioning
confidence: 96%
“…Numerous studies have identified that traditional halogen-based flame retardants are the most effective and economic flame retardants. 15,16 However, halogen flame retardants are toxic and environmentally harmful. Resultantly halogen-free flame retardants have been focused on to a greater extent based on their environmental friendliness.…”
mentioning
confidence: 99%
“…LDHs present good flame retardant properties and smokesuppressing properties due to its special structure and chemical component. 15 Ren et al 31 synthesized a MgFe-LDHs, after which LDHs and APP were introduced into the TPU to reduce smoke density during combustion. Their results evidenced that through combining 16 wt% APP and 4 wt% LDHs, the maximum smoke density (D s,max ) declined from 222.5 to 44.0, suggesting that LDHs within a polymer matrix offer effective smoke-suppression.…”
mentioning
confidence: 99%